Student agency in volunteer programmes at Rhodes university - Mdluli, Siphiwayinkosi (University of the Witwatersrand, Johannesburg, 2024)
Student volunteer work plays a vital role in addressing local community issues such as high poverty rates, high illiteracy and high unemployment rates. Through students, tertiary institutions are able to fulfil their social responsibility. The purpose of this study was to explore the role of agency on student participation in volunteer work at Rhodes University, in Makhanda. To effectively respond to this inquiry, the research focused on the Nine Tenths Mentoring programme. Following a qualitative approach comprising a mix of an interpretivist and case study paradigms, the findings revealed that the umbrella term ‘student agency’ comprised mainly of moral agency, identity agency, pragmatic agency, and existential agency. These forms of agency largely contributed to a positive volunteer experience that contributed significantly to healthy relationships among community members and student volunteers, as well as advancing the student volunteers as committed agents of social change. This research highlighted the importance of involving tertiary students in community volunteer work.
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; AGENCY; COLLECTIVE AGENCY; EXISTENTIAL AGENCY; IDENTITY AGENCY; MORAL AGENCY; PERSONAL AGENCY; PRAGMATIC AGENCY; SOCIAL AGENCY; STUDENT AGENCY; VOLUNTEERISM; SDG-4: Quality education